Both sides of the equation have something different happening. I would start by distributing the -2 into the right side. Your problem will look like this:

11-(6x-3)=-4x-10

Next we need to eliminate the parenthesis on the other side. Notice that we don't distribute the 11, since it is not being multiplied into the set. However, we can't just "drop" the parenthesis either. When we do, our 6x becomes -6x. We need to look at the problem like this:

11-**1**(6x-3)=-4x-10.

One times whatever is in the parenthesis still gives us the numbers in the parenthesis, but because the one now has a minus in front of it, the signs inside the parenthesis change. Our new problem looks like this:

11-6x+3=-4x-10

Now it is just a matter of collecting like terms and solving for x:

-6x+14=-4x-10

-2x+14=-10

-2x=-24

x= 12

------------------------

Steve S. was correct. Thanks! I should wake up before I try to do algebra!